PENGARUH KARAKTERISTIK KOMITE AUDIT PADA PENGUNGKAPAN ETIKA SUKARELA - Laili Salsabila; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2020)
The purpose of this study is to examine the influence of audit committee characteristics such as audit committee expertise, frequency of meeting of audit committee, audit committee size, audit committee tenure, dan multiple directorship of audit committee member on voluntary ethics disclosure in Indonesian companies.The population in this study were all companies registered in Indonesia Stock Exchange for the year 2018. The sampling method used in this research was purposive sampling. Total number of samples used in this study were 98 study samples. The data used in this study were obtained from companies’ annual report. The data in this study were analyzed using multiple regression techniques. The data in this study were also analyzed using classical assumption test before they were analyzed using multiple regression techniques. Other than classical assumption test, the data in this study were also analyzed using pearson correlation test. The results of this study indicate that audit committee expertise have no effect on voluntary ethics disclosure. While frequency of meeting of audit committee, audit committee size, audit committee tenure have positive effect on voluntary ethics disclosure and multiple directorship of audit committee has negative effect on voluntary ethics disclosure.